Design of an electrically small printed square loop antenna for closely spaced Tx/Rx systems - Nhat Truong; Sanghamitro Das; Satish K. Sharma (IET Microwaves, Antennas & Propagation)
Abstract A highly miniaturised electrically small square loop antenna has been designed for operation at 2.5 GHz. The antenna is loaded using a simple series combination of two lumped inductors and two interdigitated capacitors in order to realise inherent impedance matching at a given miniaturisation level with respect to a specified source impedance, without using any external matching network. The designed antenna has an overall size of 0.061λ0 × 0.061λ0, which is approximately 75.6% miniaturised in terms of total loop length and 94% miniaturised in terms of overall footprint. The designed antenna is fabricated and the corresponding impedance matching and radiation patterns are measured, which are found to be in reasonable agreement with their simulated counterparts. Moreover, an investigation with two closely spaced electrically small SLAs, one for transmitting and the other for receiving, is carried out in this work in pursuit of maximising the isolation, which plays a crucial role in the Tx/Rx systems.